PENINGKATAN KETRAMPILAN DAN PENDAMPINGAN KADER KESEHATAN DALAM MANAGEMEN LAKTASI DI DESA JETIS KAB. SUKOHARJO - M. Maryatun; I. Indarwati; S. Suparmi (P3M Universitas Aisyiyah Surakarta, 2019)
Background of study: Postpartum services consisting of breast care and lactation management must include recommending breastfeeding to the puerperal mother. The success of lactation management can be effected by a health promoter who is close to the community, known as health cadres. Jetis Village has 32 health cadres who have never received any training on proper breastfeeding techniques and breast care as an effort to promote love for breastfeeding, hence the cadres’ limited knowledge. Objective: To improve cadres’ knowledge and skills about proper breast care and breastfeeding techniques.. Method: This activity is conducted in 3 (three) stages, including socialization, training on breast care and proper breastfeeding techniques and assistance. Result: 72% of cadres can perform breast care procedures well, and 86% of the cadres can perform the skills of breastfeeding excellently. Conclusion: Health cadres’ knowledge and skills increase in breast care and correct breastfeeding techniques for infants. Cadres with the right knowledge and skills will be able to help the management of mothers after childbirth for breast care and breastfeeding techniques.